PENYULUHAN PENCEGAHAN DAMPAK JANGKA PANJANG INFEKSI SALURAN KEMIH PADA REMAJA DESA KAWATU - Tubalawony, Syulce Luselya; Lilipory, Mevi; Manuhutu, Feby; Parinussa, Nenny (Insanta : Jurnal Pengabdian Kepada Masyarakat, 2024)
Urinary Tract Infection (UTI) is a disease of the urogenital system caused by bacterial colonization of the urinary tract. The bacteria that are often found in UTI patients are E. coli bacteria. UTIs are more commonly found in teenagers and early adults, namely girls (79%) than boys (21%). UTI problems can result in increased morbidity (illness) rates which can lead to increased medical costs. Based on this problem, it is necessary to carry out prevention efforts from an early age, one of which is providing counseling through Community Service (PKM) activities to middle school (SMP) students. The aim of PKM is to provide education to Kawatu Middle School students. This activity was carried out in Class 8 of Kawatu Middle School and was attended by 35 students and 2 teachers. This activity stage includes preparation, implementation and evaluation of the program. The results of this activity showed that there were 19 (75.4%) female students while there were 16 (24.6%) male students. During the counseling process, interactive questions and answers occur, showing that students are able to receive the material well. The conclusion is that this PKM activity was successful in increasing students' knowledge regarding the occurrence and prevention of UTIs and their complications if they are not handled thoroughly.